Synthesis and Characterization of Phenolic Resole Resins for Adhesive Applications - Gouranlou, Farideh (Asian Journal of Chemistry, 2010)
In present studies, the phenol-formaldehyde resole resins have been synthesized in the presence of sodium hydroxide as catalysts. The activity of these catalysts was compared with the activity of barium hydroxide and ammonia. 1H and 13C NMR spectrometry and some physico-chemical methods were used to estimate the composition of the obtained resins and their properties. It was concluded from these studies that sodium hydroxide is active catalysts and the resins obtained in their presence show some interesting properties.